BRIDGING KNOWLEDGE AND INNOVATION: THE ROLE OF ARTIFICIAL INTELLIGENCE ON RESOURCE ALLOCATION MANAGEMENT IN PUBLIC UNIVERSITIES IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2025)
This study was guided by three research questions and three hypotheses. It adopted a descriptive survey design. The population of the study comprised of 7,064 employees in two public universities in Anambra state. Stratified random sampling was used in selecting 232 staff (male 109, female 123) as sample. The instrument for data collection was a structured questionnaire titled “Role of Artificial Intelligence on Resource Allocation Management in Public Universities Questionnaire (RAIRAMPUQ)”. It was drafted from the three research questions. The instrument was validated by 3 experts. The reliability was established using 20 university staff who were not selected as sample for this study. The test-retest technique was used for the process. Cronbach Alpha technique was used to compute the result which yielded reliability coefficient values of 0.83, 0.80 and 0.75 with a general index of  0.79 and thus, confirmed the instrument reliable. The questionnaires were distributed and collected at the spot. A total of 255 questionnaires that were distributed, only 232 were fully filled and retrieved. The data collected were analyzed using mean and standard deviation while t-test was used to test the hypothesis at .05 level of significance. Findings show that Artificial Intelligence play significant role in human, material and financial resources of public universities. In human resource management, AI helps in the enhancement of staff engagement, aids in analysing employee data to identify potential individuals, helps students carry out their academic activities, recruitment of employees and staff development. The study recommends among all that human resource in Nigerian universities be annually trained to the mastery of computer so that they can effectively utilize opportunities in AI to perform their academic duties professionally.
Keywords: Knowledge, Innovation, AI, Resource Allocation, Management